Economy and Society: An Outline of Interpretive Sociology (an excerpt) - Weber, Max (Journal of Economic Sociology, 2018)
This section presents the third volume of Max Weber’s fundamental work Economy and Society which has been translated into Russian for the first time. The third volume includes two works devoted to the sociology of law. The first, ‘The Economy and Laws’, discusses differences between sociological and juridical approaches to studies of social processes. It describes peculiarities of normative power arenas (orders) at different levels and demonstrates how they influence the economy. The second, ‘Economy and Law’ (‘Sociology of Law’) , reviews the evolution of law orders (primarily, the three “greatest systems of law” including Roman Law, Anglo-American Law, and European Continental Law) in the context of changes in the organization of economy and structures of dominancy. Law is considered an influential factor of the rationalization of social life which in turn is affected by a rationalized economy and social management. The Journal of Economic Sociology here publishes an excerpt from the chapter ‘Law, Convention and Custom’ in this third volume, which shows the role of the habitual in the formation of law; explains the importance of intuition and empathy for the emergence of new orders; and discusses the changeable borders between law, convention and custom. The translation is edited by Leonid Ionin and the chapter is published with the permission of HSE Publishing House.